Validity of powerpoint-ispring learning media on carbohydrate materials in high school - Mila Lestari; Guspatni Guspatni (Jurnal Pijar Mipa, 2023)
Carbohydrate material is a theoretical chemical that connects every concept to make it seem abstract. It resulted in students needing help understanding the material. Learning media can help students understand the material, which can display animations, pictures, and videos. One learning media that can display this is the PowerPoint-iSpring learning media. This study aimed to determine the validity value of PowerPoint-iSpring learning media on carbohydrates for class XII high school students. This research is educational design research using the Plomp model. The subjects of this study were three chemistry lecturers at the Chemistry Education Study Program, Faculty of Mathematics and Natural Sciences, Padang State University and two high school chemistry teachers, and class XII students at SMAN 7 Padang. The instruments used were teacher interview sheets, student questionnaires, and validity test questionnaires. The type of data is primary data which was analyzed using Aiken's V formula. The results of this study obtained a content validity test of 0.85, construct validity of 0.81, and media validity of 0.81. In conclusion, the learning media developed could be categorized as valid.